Study of Social Mobility in Sociology: समाजशास्त्र में सामाजिक गतिशीलता का अध्ययन - Yadav, Deepika (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Mobility is a social fact. In sociology, the study of social mobility is conducted in the context of social stratification and social change. Generally, the movement of individuals, and sometimes entire groups, between different positions or levels is referred to as social mobility. In other words, social mobility indicates changes in the structure of positions. For example, a poor individual becoming wealthy through business success or a teacher contesting elections and becoming a minister represents social mobility. Abstract in Hindi Language: गतिशीलता एक सामाजिक तथ्य है। समाजशास्त्र में सामाजिक गतिशीलता का अध्ययन सामाजिक संस्तरण एवं सामाजिक परिवर्तन के सन्दर्भ में किया जाता है। सामान्यतः व्यक्तियों का और कभी-कभी किसी सम्पूर्ण समूह की भिन्न प्रस्थितिों अथवा स्तरों के बीच होने वाले परिवर्तन को सामाजिक गतिशीलता कहते है। अर्थात सामाजिक गतिशीलता संरचना में प्रस्थितियों के परिवर्तन का संकेत देती है। उदाहारण के लिए किसी गरीब व्यक्ति द्वारा व्यवसाय में सफल होकर अमीर बन जाना या किसी शिक्षक द्वारा चुनाव लड़कर मंत्री बन जाना सामाजिक गतिशीलता को दर्शाता है। Keywords: जातीय समाज, सामाजिक गतिशीलता, परिवर्तन, वर्ग समाज